2021
DOI: 10.32098/mltj.03.2021.25
|View full text |Cite
|
Sign up to set email alerts
|

Injury risk and maturity status in Italian elite young football player

Abstract: Background. Football is one of the world's most popular sport with most players being younger than 18 years. Playing football can induce beneficial health effects in youth, but there is also a high risk of injury. In young football players, the relationship between injury risk in the different periods from peak height velocity (PHV) remains unclear. The objective of the study was to investigate the associations between the injury risk and injury burden in young Italian football players in different periods fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…One approach to determining the extent of injuries is to count how many players sustain at least one injury over a season. In boys, this has ranged from 38 to 85% ( 18 25 ), with 0.4–2.2 injuries per player per season ( 19 42 ). Only one study reported seasonal injury proportion for girls (37%) ( 43 ), with another finding an average of 4.3 injuries per player per season ( 44 ).…”
Section: Injury Patterns In High-level Youth Footballmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach to determining the extent of injuries is to count how many players sustain at least one injury over a season. In boys, this has ranged from 38 to 85% ( 18 25 ), with 0.4–2.2 injuries per player per season ( 19 42 ). Only one study reported seasonal injury proportion for girls (37%) ( 43 ), with another finding an average of 4.3 injuries per player per season ( 44 ).…”
Section: Injury Patterns In High-level Youth Footballmentioning
confidence: 99%
“…Expressing injuries relative to training and match hours is therefore recommended. Using the median of point estimates for reported injury rates (this does not consider the size of each study, nor the uncertainty in their estimates) and keeping methodological differences in mind, the number of injuries per 1,000 h appears similar between genders ( Figure 1 ): around 6.3 (range: 1.3–12.1) for boys ( 18 20 , 24 , 26 , 27 , 29 , 31 – 33 , 36 , 37 , 41 , 42 , 46 – 57 ) and 6.4 (2.1–9.1) for girls ( 44 , 55 , 58 60 ). Matches are consistently associated with greater risk compared to training sessions in both boys (match: 13.4, training: 4.0) and girls (match: 22.4, training: 4.6) ( 18 20 , 24 26 , 29 , 31 – 33 , 36 , 42 , 46 – 50 , 53 55 , 58 , 60 63 ).…”
Section: Injury Patterns In High-level Youth Footballmentioning
confidence: 99%
“…Evidence of higher injury incidence, particularly microtraumatic damage to tissue (e.g., bone; muscle; tendon) during the period of PHV and increased general injury burden (15 vs 7 days) compared to pre-PHV (when the rate of growth in stature is at its slowest) [12] is reported in European youth soccer players [13]. Similarly, in a professional, male, Italian soccer academy, the highest injury incidence across academy age groups was reported in the U13 years, followed by the U15 and U14 years, corresponding to the period of PHV, yet caution is warranted when interpreting these findings as they are derived from a single club in Europe [14]. It would appear professional soccer clubs worldwide are becoming increasingly invested in monitoring injury rates and growth patterns of their players, particularly around PHV, due to the associated increases in injury risk, incidence, and severity that predispose players during this period [15,16].…”
Section: Introductionmentioning
confidence: 95%
“…From a holistic perspective, practitioners and researchers in this field may need to look beyond simply the methods they employ to assess maturational status and timing in academy soccer players and consider the wider implications of their choices on issues such as PLOS ONE injury risk. Recent work has highlighted an increase in injury risk and incidence around reported mean ages (i.e., 13-14 years) at PHV [11,14]. Furthermore, the growth spurt coupled with its maturity-associated variations are among some of the injury risk factors for the developing male athlete [10].…”
Section: Suggestions For Future Studiesmentioning
confidence: 99%